Multi-level exploration of value co-creation in a service ecosystem : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Marketing at Massey University, Albany, New Zealand - Patara, Anushka (Massey University, 2024)
This doctoral study explores multi-level value co-creation in a sustainable fashion service ecosystem in New Zealand, guided by the theoretical lens of service-dominant logic and an ecosystems perspective. It critically examines how actors at the macro (experts), meso (a sustainable fashion retailer), and micro (consumers) levels co-create value. An interpretive qualitative design was employed, drawing on 34 in-depth interviews across macro, meso and micro levels, with data analysed using reflexive thematic analysis. The analysis identified four interrelated pathways to value co-creation – knowledge, future orientation, guardianship, and regeneration – and seven contextual factors shaping value outcomes. Promoting longevity, impact reduction, and a conscious consumption approach facilitates co-creation, whereas knowledge anxiety, limited accessibility, and inadequate infrastructure and regulation constrain it, creating conditions for value co-destruction despite pro-sustainability intentions. This study contributes to the service ecosystem and sustainability marketing literature by proposing a multi-level value co-creation framework, which reveals how actors’ sensemaking and resource integration are conditioned by broader structural, institutional, and material contexts. It highlights the misalignments and tensions across levels that lead to fragmented efforts and limited systemic impact. By unpacking the interplay between actor narratives, practices and contextual constraints, the study offers insight into how sustainable transformation is both enabled and undermined. The findings inform the theoretical understanding of value co-creation in service ecosystems that are sustainable or transitioning towards sustainability. Practically, they offer guidance for businesses, policymakers, and leaders seeking to orchestrate more coherent, cross-level strategies for sustainable fashion. This research confirms that value co-creation is not just an outcome but an ongoing, negotiated process within complex and evolving ecosystems.
Keywords: Value Co-Creation, S-D Logic, Service Ecosystem, Sustainable Fashion; 330314 Sustainable design; 350602 Consumer-oriented product or service development